IMPLEMENTASI AKAD ISTISHNA PADA HOME INDUSTRY MAMA AWAH JAHIT DI KELURAHAN SUMURPECUNG KOTA SERANG - Nazwa Septiani; Fidela Syahda; Fany Cahyaningsih; Dea Anastya Putri; Mukhlishotul Jannah (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to analyze the application of the istishna contract in buying and selling transactions at the "Mama Awah Jahit" home industry in the Sumurpecung area, Serang City using a qualitative approach. Data collection was carried out through literature study, observation, interviews and documentation. The research results show that the implementation of the istishna contract in this case has fulfilled the required pillars, however there are differences in views between the Hanafi and Shafi'i schools of thought regarding the payment mechanism. This research also concludes that the istishna contract can be terminated if one party does not carry out its obligations according to the agreement. This research highlights the differences in views between the Hanafi and Shafi'i schools of thought in implementing the istishna contract. This difference shows the importance of a deep understanding of Islamic law in transactions. This research provides an important contribution in understanding the application of the istishna contract in the context of small and medium businesses, especially in home industry. The results of this research can be a reference for business actors and other researchers.